A Camel Model Analysis of private Sector Banks in India - Gupta, RK; Sibat, Sumeet Kaur (Gyan Management Journal, 2008)
All the banks in India were earlier pri ale banks. The wer found d in th pre-independence era to ca er to Lhc banking needs of th people. But aflcr nationalization of bank in HJ69 public ctor bank came to occupy dominant role in the banking structur . Pri ate sector banking in India r cci d a fillip in 1994 when Reserve Bank of India encouraged selling up of privat banks as part of ils policy of lib ralization of th Indian Banking Industry. Housing Development Financ Corporation Limited (HDFC) was am ngst the first to receive an in principl ’ appro al fr m the R serv Bank of India (RB I) lo el up a bank in th pri at se tor.